Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

x^2 - 6x + 1 = 0 by completing the square​

Sagot :

Answer:

See below.

Step-by-step explanation:

x^2 - 6x + 1 = 0

x^2 - 6x = -1

We halve the coefficient of  x (which is -6/2 = -3) and square it, then add this to both sides:-

x^2 - 6x + (-3)^2 = -1 + (-3)^2

x^2 - 6x + 9 = -1 + 9

(x - 3)^2 = 8

x - 3 = ±√8

x =  3 ± √8

= 0.17, 5.83   to 2 decimal places.

Answer:

[tex]x = - 2 \sqrt{2} + 3 \\ or \\ x = 2 \sqrt{2 } + 3[/tex]

View image BrainiacHannah
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.